Earning while learning the lived experiences of undergraduate students working during term-time - Victorio, Alexa Ebyrose L. (College of Home Economics, University of the Philippines Diliman, 2022)
This study seeks to explore the experiences of Filipino working undergraduate students and identify their motivations, benefits, challenges, and adaptation. The researcher used pre-interview surveys and in-depth interviews in gathering data. The research sample of this study includes 10 Filipino respondents aged 18 to 25 years old who are working while studying in the National Capital Region. The results show that working undergraduate students are mainly motivated by financial needs, while the benefits identified are compensation, intrapersonal skills, interpersonal skills, and professional skills. On the other hand, the challenges identified are divided into the following domains: (1) self, which involves exhaustion and stress, lack of sleep, and depression, anxiety, and insecurities; (2) school, which involves workload-related challenges, grades-related challenges, inconsiderate professors, and challenges with the continuation of studies; (3) work, which involves inflexible work, managing clients or customers, incompetence, and challenges inherent in work type; (4) school and work, which involves conflicting schedules; and (5) family, which involves lack of recreational time with family, lack of time for chores, financial problems within the family, and communication problems with the family. This study also identified adaptation strategies in overcoming these challenges which are divided into the following categories: (1) activities, (2) intrapersonal skills, (3) interpersonal skills, (4) work-related skills, and (5) external sources of support. With these findings, the society can better understand the contexts of working students in the country to provide better services towards them.